The ATS/ERS/JRS/ALAT Statement "IPF by HRCT" could Predict Acute Exacerbation of Interstitial Lung Disease in Non-small Cell Lung Cancer. Issue 1 (January 2017) - Asai, Nobuhiro; Katsuda, Eisuke; Hamanaka, Rie; Kosaka, Kenshi; Matsubara, Ayako; Nishimura, Masaki; Tanaka, Hiroyuki; Yokoe, Norihito; Takahashi, Ayumu; Yamaguchi, Etsuro; Kubo, Akihito
Introduction: Patients with non-small cell lung cancer (NSCLC) and interstitial lung disease (ILD) are at high risk of acute exacerbation of ILD (AE-ILD) when treated with systemic chemotherapy. Standard treatment for NSCLC complicated by ILD has not been established. Purpose and methods: To examine whether the type of ILD categorized by the official ATS/ERS/JRS/ALAT statement as "idiopathic pulmonary fibrosis (IPF) by high-resolution computed tomography (HRCT)" could predict chemotherapy-induced AE-ILD in NSCLC patients with ILD, we retrospectively reviewed all patients with NSCLC complicated by ILD who had received chemotherapy at our institute from January 2007 until December 2013. Patients' characteristics, pathology and clinical staging of lung cancer, chemotherapy, type of ILD and AE-ILD during chemotherapy were evaluated. ILD was classified according to the statement as follows: usual interstitial pneumonia (UIP), possible UIP, and inconsistent with a UIP pattern. Results: A total of 46 patients had pre-existing ILD and received chemotherapy. The mean age was 73 years (range 46-83 years). Fifteen (32.6%) of 46 patients with ILD developed chemotherapy-induced AE-ILD, which was seen more frequently in patients with ILD with a UIP pattern or possible UIP pattern than in patients with a pattern inconsistent with UIP (80% versus 9.7%, p<0.001). Multivariate analyses including age, sex, performance status and radiographic patterns of ILD showed that the presence of a UIP or possible UIP pattern was an independent risk factor for chemotherapy-induced AE-ILD. Conclusions: ILD with a UIP pattern or possible UIP pattern by the classification could be a risk factor for AE-ILD in NSCLC patients with ILD.